Halal Travel Research Development - Nadia Nurul Izza (SMART Insight, 2021)
According to the State of the Global Islamic Economic report by Thomson Reuters in collaboration with Dinar Standard, the global Muslim market destination was valued at 140 billion in 2013, representing 11.5% of global spending. The same report also shows that the segment was worth 238 billion in 2019 and represented 13% of global spending. The Muslim consumer market has been recognized as another important segment for cross-sectoral businesses. The increasing interest has made researchers begin to focus their research on halal tourism. The increasing population and purchasing power of Muslims around the world, as well as the new era of modernization reinforce the trend of increasing halal lifestyle in tourism. Sharia values ​​will be more practiced as a way of life by seeing this condition the global market must respond to the needs, preferences, and unique market orientations as well as economic values ​​and trade. One of the halal lifestyle trends in Indonesia currently consists of the tourism sector, namely Halal Travel. This study aims to determine the development map and trends of Halal Travel. The data analyzed were more than 67 Scopus indexed research publications. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric map of the development of Halal Travel. The results of the study show that the number of publications on the development of the role of Halal Travel research continues to increase.